Analysis of the TAIGA-HiSCORE data. (December 2020) - Samoliga, V
Abstract: TAIGA-HiSCORE is an extensive air shower array of 120 Cherenkov detectors spread over an area of 1 km 2 . It is designed to detect cosmic rays with energies from 50 TeV to 1000 PeV. Also TAIGA-HiSCORE is planned to use for gamma-ray astronomy in cooperation with the other installations of the TAIGA observatory. This work is dedicated to the analysis of the TAIGA-HiSCORE single-mode data. We consider a possibility to detect gamma-ray point source with excess of events from the source direction. For this purpose, a method for estimation of the signal significance is proposed. It takes into account the angular acceptance of the TAIGA-HiSCORE installation. The method is tested on the Monte-Carlo toy model.